Analysis of Organisational Culture, Work Environment, and Leadership Style through Innovation on Employee Performance - Asrianto (Cendekiawan Indonesia Timur, 2024)
This study aims to analyse the influence of organisational culture, work environment, and leadership style through innovation on employee performance at PT Telkomsel Branch Makassar. This company faces challenges in maintaining productivity and achieving the expected targets, marked by fluctuations in employee performance in various regions. Factors such as less than optimal organisational culture in supporting innovation, an uncomfortable work environment, and a leadership style that is not optimal are thought to contribute to the decline in performance. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to employees of PT Telkomsel Branch Makassar. The variables studied include organisational culture, work environment, leadership style, innovation, and employee performance, with multiple linear regression analysis used to test the relationship between variables. The results showed that an organisational culture that supports innovation and a conducive work environment significantly influenced the improvement of employee performance. A participative leadership style also positively contributes to increased innovation and team collaboration. Innovation acts as a mediating variable that strengthens the relationship between organisational culture, work environment, and leadership style on employee performance. The findings provide important implications for companies in creating a more innovative environment and supporting employee growth, in order to achieve sustainable competitive advantage.